Pathogen-Host Interactions: Antigenic Variation v. Somatic Adaptations - Hsu, Ellen; Du Pasquier, Louis; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume provides in-depth reviews of model systems that exemplify the arms race in host-pathogen interactions. Somatic adaptations are responsible for the individualization of biological responses to the environment, and the continual struggle between host immune systems and invading pathogens has given rise to corresponding processes that produce molecular variation. Whether in mollusks or human beings, various host somatic mechanisms have evolved independently, providing responses to counter rapidly-changing pathogens. The pathways they utilize can include non-heritable changes involving RNA and post-translational modifications, or changes that produce somatic DNA recombination and mutation. For infectious organisms such as protozoans and flatworms, antigenic variation is central to their survival strategy. Evolving the ability to evade the host immune system not only increases their chances of survival but is also necessary for successful re-infection within the host population.
Evolution of immunity and pathogens -- A host-pathogen interaction reduced to first principles: Antigenic variation in T. brucei -- Antigenic variation in Plasmodium falciparum -- Polymorphic mucin-like proteins in Schistosoma mansoni, a variable antigen and a key component of the compatibility between the schistosome and its snail host -- Fibrinogen-related proteins (FREP) in mollusks -- Somatic and germline diversification of a putative immunoreceptor within one phylum: Dscam in arthropods -- An immune effector system in the Protochordate gut sheds light on fundamental aspects of vertebrate immunity -- Variable lymphocyte receptors: a current view -- Antibody repertoire in fish -- Unique features of fish immune repertoires: particularities of the adaptive immunity within the largest group of vertebrates -- The evolution and structure of atypical T cell receptors -- Diversification of the primary antibody repertoire by AID-mediated gene conversion -- Antibody isotype switching in vertebrates.
Keywords: Medicine; Immunology; Parasitology; Cell biology; Evolutionary biology; Biomedicine; Immunology; Evolutionary Biology; Cell Biology; Parasitology; Electronic books